Upaya Baitul Maal Wa Tamwil Bertahan Di Masa Pandemi Covid-19 - Muhamad Fauzi; Agus Gunawan; Ahmad Darussalam (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
Background: The middle economics in Indonesia, has been familiar with Baitul Maal Wat Tamwil (BMT), it is presenting needs supports of many people. During the Covid-19 pandemic, economic activities has limitations and obstacles, including BMT trying and finding out scheme alternatives to survive in providing services. Purposes: The purpose of this study is to find out the efforts of BMT to survive the Covid-19 pandemic. Methods: This study used a literature review with a descriptive approach and triangulation analysis techniques. Results: The results showed: the characteristics of BMT in the middle society still exist even though in times of crisis, the level of public confidence in BMT providing alternative financing, government policies has focus on saving Islamic financial institutions, the existence of BMT development policies are liquidity is a priority, monitoring of deposits liquidity, and controlling lending or financing as efforts BMT surviving liquidity supporting, relaxation, social safety nets, task force handling the impact of Covid-19 in the Islamic microfinance sector, deposit insurance microfinance institution (LPS), supervision and effective reporting, digital business ecosystem by human touch and technology. Conclusions: Thus, the efforts BMT surviving by digital business application and information technology, government support and management internalization.